Evaluations of Novel Waveform Coding Signals Based on Finite Projective Plane - Chien-Hsing Liao; Tai-Kuo Woo; Chi-Chung Chen; Ing-Jiunn Su (电子科技学刊, 2016)
The most popular and representative classic waveform codes are referred to as orthogonal, bi-orthogonal, simplex, and etc, but the choice of waveform codes is essentially identical in error performance and cross correlation characteristic. Though bi-orthogonal coding requires half the bandwidth of the others, such coding scheme is attractive only when large bandwidth is available. In this paper, a novel finite projective plane (FPP) based waveform coding scheme is proposed, which is with similar error performance and cross correlation. Nevertheless, the bandwidth requirement will grow in a quadratic way, but not in an exponential way with the values of message bit numbers (k). The proposed scheme takes obvious advantages over the bi-orthogonal scheme whenk≥ 6.